Methodological Support for Inventory Analysis at Ukrainian Trade Enterprises: Current State and Directions for Improvement - Lazaryshyna, I. D.; Sichkar, I. O. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article presents the results of a study on the current state of methodological support for inventory analysis at trade enterprises in Ukraine. Existing approaches to building analytical systems are critically assessed, and directions for their improvement are proposed in line with the challenges of digitalization, increased informational load on accounting systems, and the needs of strategic management. It is substantiated that the current approaches are fragmented, do not take into account industry specifics, external risks, or technological changes in accounting, which reduces the informativeness of analytical indicators and complicates decision-making. Three key methodological aspects are identified: defining the boundaries of the analysis system, rules for cost allocation between inventory flows, and standards for data quality and assumptions. It is shown that insufficient attention to these aspects leads to distorted results, a loss of repeatability in analytical procedures, and reduced management effectiveness. The authors propose a concept of comprehensive methodological support, which involves the integration of accounting, analysis, and control functions into a unified ERP-class digital environment, along with the use of adaptive algorithms. The following components have been developed: (1) an algorithm for defining system boundaries, taking into account logistics and reverse-utilization processes; (2) a cost allocation model based on utility and value indicators; and (3) a data quality matrix indicating sources, representativeness, and assumptions. A multi-factor inventory classification based on time, price, demand, and function is proposed, enabling detailed analysis tailored to specific management objectives. It is proved that these solutions enhance the reliability of analytical conclusions, facilitate risk identification, optimize inventory-related costs, and contribute to increased profitability of turnover. It is concluded that forming a modern methodology for inventory analysis is not only a tool for improving accounting efficiency, but also a strategic resource for achieving flexibility, resilience, and competitiveness of trade enterprises in a post-crisis economy. The article summarizes key requirements from national regulatory documents and current scientific-practical publications on inventory analytics, and outlines directions for their adaptation to the present conditions of trade enterprises. Typical issues such as formalized analysis, fragmented data sources, and the lack of clear cost allocation methods are considered from the perspective of improving methodological support. Their resolution is proposed through the use of digital tools, integration of accounting, analysis, and control functions within a single information environment, and the revision of internal enterprise regulations.